Amyloid beta directed antibody for Alzheimer's disease, an evidence based meta-analysis - Li, C; Ma, Q; Chen, S; Feng, J; He, Y (Cellular and Molecular Biology, 2016)
In several preclinical researches, antibody of Aacting directly in the central nervous system showed a great efficacy on the clearance of plaques. However, the other researches were opposite. We performed a meta-analysis to evaluate the amyloid-beta-directed antibody treatment of Alzheimer's disease. We searched Pubmed, Web of science, Embase and Cochrane library. Pooled data was calculated by standard mean difference. The heterogeneity and publication bias were evaluated by I2 and funnel plot. Totally, 5 RCTs (randomized clinical trials) with high qualities were included. There weas no difference of mean change form baseline between therapy and placebo group based on Mini-Mental State Examination (MMSE, SMD = 0.00, p = 0.97, 95% CI = -0.23 0.22) and Clinical Dementia Rating–Sum of Boxes (CDR-SB, SMD = 0.22, p = 0.39, 95% CI = -0.28 0.71), but a significant decrease according to Alzheimer's Disease Assessment Scale (ADAS-cog, SMD = 0.07, p = 0.01, 95% CI = -0.02 0.13). In conclusion, Antibody was not benefit for AD based on MMSE and CDR-SB but had a little effect according to ADAS-cog.